Enabling single qubit addressability in a molecular semiconductor comprising gold-supported organic radicals. Issue 5 (28th November 2018) - McGuire, Jake; Miras, Haralampos N.; Richards, Emma; Sproules, Stephen
Abstract : An organic radical attached to gold represents an electrically addressable prototype electron spin qubit with an impressively long coherence lifetime. Abstract : A bis(dithiolene)gold complex is presented as a model for an organic molecular electron spin qubit attached to a metallic surface that acts as a conduit to electrically address the qubit. A two-membered electron transfer series is developed of the formula [Au III (adt)2 ] 1−/0, where adt is a redox-active dithiolene ligand that is sequentially oxidized as the series is traversed while the central metal ion remains Au III and steadfastly square planar. One-electron oxidation of diamagnetic [Au III (adt)2 ] 1− (1 ) produces an S = 1/2 charge-neutral complex, [Au III (adt2 3− ˙)] (2 ) which is spectroscopically and theoretically characterized with a near negligible Au contribution to the ground state. A phase memory time ( T M ) of 21 μs is recorded in 4 : 1 CS2 /CCl4 at 10 K, which is the longest ever reported for a coordination complex possessing a third-row transition metal ion. With increasing temperature, T M dramatically decreases becoming unmeasurable above 80 K as a consequence of the diminishing spin-lattice ( T 1 ) relaxation time fueled by spin–orbit coupling. These relaxation times are 1–2 orders of magnitude shorter for the solid dilution of2 in isoelectronic [Ni(adt)2 ] because this material is a molecular semiconductor. Although the conducting properties of this material provide efficient pathways to dissipate the energy through the lattice, it can also be used to electrically address the paramagnetic dopant by tapping into the mild reduction potential to switch magnetism "on" and "off" in the gold complex without compromising the integrity of its structure. These results serve to highlight the need to consider all components of these spintronic assemblies.